Introduction to the Special Issue on the Impact of Placement on Outcomes for Students with Complex Support Needs. (December 2022) - Kurth, Jennifer A.; Jackson, Lewis
The papers for the December 2022 special issue focused on outcomes of placement for students with complex support needs. We also describe the purpose of the overall study, student participants, research questions, and why placement is an important consideration in determining student outcomes.